Nilai-Nilai Keagamaan dalam Tradisi Panggih Masyarakat Desa Rantau Durian Ogan Komering Ilir (Program Studi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Pemikiran Islam, 2021)
This article is entitled “Religious Value In The Panggih Tradition Of The Rantau Durian Village Community”. Marriage is a sacred, great and very monumental activity for every couple living in this world. Therefore, marriage is not only following religion but marriage continues the instincts of the ancestors to be able to form a family in a legal relationship between a man and a woman, and has a very deep and broad meaning for human life in leading to the life it wants. Panggih ceremony is a series of Javanese traditional wedding ceremonies of the call, panatacara usually uses native Javanese language, so that not all listeners are able to understand the contents of the panatacara, the problem in this research is what are the religious values in the tradition of calling the village community Rantau Durian, Lempuing Jaya district, research this study aims to determine the religious values in the panggih tradition, the problem of the Rantau Durian, village, Lempuing Jaya sub district, Ogan Komering Ilir district. As for the research used in this is the type of field research, qualitative data types, data sources, primary, data sources, secondary data sources, data collection techniques, observation, interviews, documentation, qualitative data analysis techniques.The results of the analysis of research on religious values in the panggih tradition of the Rantau Durian village community, for Javanese, traditional brides include the value of respect, the value of devotion, the value of justice, the value cleanliness, the value of responsibility, and the value of the work. These values are all from the results of the researcher’s analysis, which are contained in a ritual in the activities of the panggih tradition. Keywords: Religious Values, Traditions Of Panggih.